Don’t Skirt the Subject: Using Canonical Texts as Opportunities for Race Discussion - Gardner, Emily (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
While administrators, parents, and scholars across the nation ceaselessly debate the issue of whether or not racially challenging texts, such as Adventures of Huckleberry Finn, To Kill a Mockingbird, and Heart of Darkness, should be included in English language arts curriculum, many English teachers are left to teach these controversial texts with often insufficient training in how to utilize them in their classrooms. It is the responsibility of teachers to help students become empathetic citizens by developing the skills necessary to navigate through a racially diverse world. Therefore, teachers ought to use texts containing racism as opportunities to open a conversation of race relations both in the past and present time, by using research-based methods, like those in this article.